2021
DOI: 10.1021/acsestwater.1c00331
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized MOF-Coated Zero-Valent Cu Driving an Efficient Dual-Reaction-Center Fenton-like Water Treatment Process through Utilizing Pollutants and Natural Dissolved Oxygen

Abstract: Excessive consumption of resources and energy is inevitable in a classical Fenton reaction due to the demand for electron donors or electron acceptors (H 2 O 2 ) and the existence of reaction rate-limiting steps. In this work, we propose an innovative strategy to solve this key scientific problem by utilizing the organic pollutants and the dissolved oxygen (DO) naturally present in the wastewater through a newly developed carbonized metal−organic frameworkcoated zero-valent Cu catalyst (ZVC@CMOF). It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Studies in the literature have shown that the pathway by which ROS are generated by O 2 activation involves electron-rich Cu sites facilitating electron transfer; , in this study, an analysis was performed on the change of the Cu valency state to determine whether the same activation pathway was operational. XPS was employed to characterize the chemical states of the elements involved in the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature have shown that the pathway by which ROS are generated by O 2 activation involves electron-rich Cu sites facilitating electron transfer; , in this study, an analysis was performed on the change of the Cu valency state to determine whether the same activation pathway was operational. XPS was employed to characterize the chemical states of the elements involved in the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the • OH signal intensity increased after BPA addition (Figure 5b), indicating that BPA could be adsorbed on electron-poor C sites of Co@NCNT/NC and replace H 2 O 2 as the electron donor; thus, electrons transferred to the electron-rich Co center via the electron tunneling-based C−Co charge-transfer bridge and were the driving force for more H 2 O 2 to reduce to • OH, which confirmed that the pollutants can enhance the polarization between the electron-rich and electron-poor centers and promote the reduction of H 2 O 2 . 11 In the Co@NCNT/NC+H 2 O 2 system (Figure 5c), a distinct…”
Section: Identification Of the Reactive Speciesmentioning
confidence: 99%
“…Meanwhile, the rate-determining step that the conversion from the oxidation state to the reduction state still presents a challenge for Fenton-like catalysts. , Recent research has shown that electron transfer can be accelerated in heterogeneous Fenton-like processes triggered by using light, electricity, ultrasonic-assisted excitations of electrons and adjusting the electron structure of the catalyst to improve the utilization of electrons. , Among them, constructing dual reaction centers composed of electron-rich/poor centers has been acknowledged as a more effective approach to optimize the electronic properties of catalysts. Generally, electron-rich centers provide electrons for H 2 O 2 activation, while electron-poor centers receive electrons as electron acceptors and, simultaneously, reimburse electron-rich centers through transmission channels for Fenton-like catalysis. Our recent studies have shown that the construction of dual-reaction-centers on the BiOX (X = Cl and I) interface can greatly induce the surficial/interfacial electron transfer and achieve the selective reduction of H 2 O 2 by reducing the activation energy demands and eliminating the pH constraints. , Hence, regulating the polarized electron distribution of the TM at the surface and interface of Fenton-like catalysts to promote the generation of ROS to achieve an optimized catalytic performance is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…42 It clearly showed that the relative ratio of I D /I G decreased (1.36−1.23) with the increase of dicyandiamide ratio, indicating that more N sources in precursors endowed N x /C with fewer defects, higher graphitization, and better electrical conductivity. 6 The surface properties of N x /C materials were also evaluated via N 2 adsorption−desorption analysis. As shown in Figure S14 and Table S11, all N x /C cocatalysts showed a typical mesoporous structure with an increased specific surface area from 18.607 m 2 /g of N 1 /C to 246.882 m 2 /g of N 10 /C.…”
Section: Acs Esandt Engineeringmentioning
confidence: 99%
“…Fenton and Fenton-like technologies are the most practical advanced oxidation processes (AOPs) in water purification with advantages of high efficiency, simplicity, and environmental benignity. Derived from the reaction between hydrogen peroxide (H 2 O 2 ) and Fe(II) under acidic conditions (eq ), the generated hydroxy radicals ( • OH, E 0 = 2.80 V/NHE) are capable of degrading various refractory contaminants and inactivating pathogenic micro-organisms. Importantly, the conversion of Fe(III) to Fe(II) is a rate-limiting step of the sustainable Fenton reactions (eq ). , To tackle this undesirable issue, great efforts have been made for expediting the reduction of Fe(III) in different Fenton-like systems. normalF normale ( I I ) + normalH 2 normalO 2 .25em .25em normalF normale ( I I I ) + normalO normalH + normalO normalH goodbreak0em1em⁣ k = 40 80 .25em normalM 1 normals 1 normalF normale ( I I I ) + normalH 2 normalO 2 .25em normalF normale ( I I …”
Section: Introductionmentioning
confidence: 99%